The compositional and stylistic techniques in Hendrik Hofmeyr’s Sinfonia africana and the earlier related works Gebed om die Gebeente and Afrika - Johnson, Alexander F. (University of Pretoria, 2015)
Dissertation (MMus)--University of Pretoria, 2015.